KAJIAN ETNOSAINS TRADISI GEBUG ENDE SERAYA DI DESA PATAS, KECAMATAN GEROKGAK DAN RELEVANSINYA PADA MATERI IPA SMP - Purnami Dewi, Kadek Ita; Selamet, Kompyang; Juniartina, Putu Prima (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is motivated by the limited use of local wisdom as a contextual learning resource in junior high school science. The aims of this study are to examine the ethnoscience concepts embedded in the Gebug Ende Seraya tradition in Patas Village, Gerokgak District, and to analyze their relevance to junior high school science materials. This research employs a descriptive qualitative method with an ethnoscience approach. The research subjects were selected using purposive sampling, including Gebug Ende performers, community leaders, and science teachers at SMP Negeri 5 Gerokgak. Data were collected through observation, interviews, documentation, and questionnaires, and were analyzed descriptively to identify the tools, stages of implementation, and scientific concepts contained in the tradition. The results show that the main tools used in the Gebug Ende Seraya tradition are the penyalin (a rattan striking stick) and the ende (a shield). The implementation stages include the matur piuning ritual, preparation of tools and costumes, and the performance led by a saye (referee). The ethnoscience study reveals local knowledge that can be reconstructed into scientific concepts, such as vibrations and waves, ecology, classification of living organisms, measurement, solid pressure, temperature and heat, as well as force and motion. The findings indicate that the most dominant concepts are related to the elements of force, motion, and energy, supported by the human organ system element in the junior high school science learning outcomes (Phase D). Therefore, this tradition has strong potential to be integrated as a contextual and meaningful science learning resource.